THE RELATIONSHIP OF EXPORTS, IMPORTS AND INVESTMENTS ON ECONOMIC GROWTH IN EAST JAVA - Stanty Aufia Rachmat,; Susianti,; Resi Marina,; Arman Syah Putra,; Nurul Aisyah, (Journal of Innovation Research and Knowledge, 2022)
The background of this research is how to find out the variables that affect economic growth in the city of East Java with these variables, it can be seen the shortcomings in order to improve the city of East Java into a more developed and advanced city, the method used in this research is to using the literature review method and using a survey to 100 East Java residents who needed random questions so that real answers could be found in the field or in the city of East Java, the problem raised in this study was how to find variables that could affect the city of Java. East In developing especially economic developments that are increasingly difficult during the current pandemic with this, these variables will be able to provide answers and can be improved for the city of East Java even better, the purpose of this study is to determine the right variables for Tuk can be given to the city of East Java in order to improve the city in the future, especially in the economic field. The variables are the export, import and investment variables.